2020
DOI: 10.1186/s12913-020-05449-2
|View full text |Cite
|
Sign up to set email alerts
|

Health staff experiences with the implementation of early essential newborn care guidelines in Da Nang municipality and Quang Nam province in Viet Nam

Abstract: Background: The World Health Organization (WHO) recommends early essential newborn care (EENC)-The First Embraceas a simple lifesaving procedure for newborns. The successful implementation of EENC at scale requires an understanding of health staff experiences, including facilitators, barriers, and local adaptations of EENC. This study aims to gain insight into health staff experiences with implementation of EENC guidelines after participation in training and coaching initiatives in Da Nang municipality and Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…The fact that almost 90% of the women brought BMS to the maternity facility at the time of childbirth or purchased it at or near by the facility suggests insufficient self-efficacy and unsupportive social norms related to the sufficiency of breastmilk in the first days of an infant’s life. The findings suggest the need for improving breastfeeding counseling for mothers and other family members during antenatal care, at the time of birth, and in the early days after birth, and for supporting breastfeeding through the provision of immediate and prolonged skin-to-skin contact, non-separation of the mother-baby dyad, and by reducing unnecessary cesarean sections [ 34 , 35 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that almost 90% of the women brought BMS to the maternity facility at the time of childbirth or purchased it at or near by the facility suggests insufficient self-efficacy and unsupportive social norms related to the sufficiency of breastmilk in the first days of an infant’s life. The findings suggest the need for improving breastfeeding counseling for mothers and other family members during antenatal care, at the time of birth, and in the early days after birth, and for supporting breastfeeding through the provision of immediate and prolonged skin-to-skin contact, non-separation of the mother-baby dyad, and by reducing unnecessary cesarean sections [ 34 , 35 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 qualitative studies, only two (Majra & Silan, 2016;Rana et al 2019) did not provide sufficient data to substantiate the interpreted results. One study had data collection method limitations because the sampling was convenient and the sample size was too small for the results to be generalised (Morseth et al 2020). Of the 13 quantitative studies, three (Abdu et al 2019;Berhe et al 2017;Tasew et al 2019) did not report selection criteria clearly and three (Abdu et al 2019;Ayenew et al 2020;Chanie et al 2021) did not consider confounders or apply appropriate methods to control for confounders.…”
Section: Results Of Quality Assessmentmentioning
confidence: 99%
“…As WHO indicates, high-quality health care can encourage mothers to adopt pro-health behaviours [ 31 ]. Further, in Viet Nam, some private hospitals regarded EENC as a special service that attracted pregnant women seeking high-quality antenatal and childbirth care [ 18 ]. To optimize the experience of postpartum mothers and improve the quality of health services, efforts should be taken to make SSC available to all mothers and neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Frederick AC et al revealed that health staff shortages were also perceived as a challenge to the implementation of EENC practices in our pilot hospitals, leading to interruptions in health worker support for sustained SSC. [ 18 , 40 ] Since regional disparities between western rural counties and urban areas in economically developed provinces in China remain high, the allocations in equipment supplied to western health facilities should be increased (e.g., maternity wards, radiant warmers, and neonatal resuscitation equipment) [ 41 , 42 ]. In our present study, most postpartum mothers had junior high school or lower education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation